Automatic behavior and communication due to pramipexole. Issue 1 (December 2016) - Walker, Ruth
Abstract A 45–year-old woman reported automatic behaviors and communication whilst she was being treated with pramipexole. These episodes vanished after the medication was tapered and she was started on levodopa/carbidopa. I hypothesize that the episodes were related to disordered awareness due to sleep disruption related to this medication.